The fruited plain : fables for a postmodern democracy - Kernan, Alvin B. (Yale University Press, 2002)
The Joad family of Steinbeck's 'Grapes of Wrath' struggled in an era of disappointed dreams and empty pockets. But how might the grandchildren of that Dust Bowl generation fare in today's more promising times? Find out in 'The Fruited Plain'.